Open-Source Horizons (IntechOpen, 2024)
Open-Source Horizons - Challenges and Opportunities for Collaboration and Innovation dives into the world of open-source research and collaboration, exploring its impact beyond software development. This book brings together a range of voices to examine the exciting potential and ongoing challenges. You can read along to explore how open-source fosters innovation, empowers individuals and ensures wider access to knowledge. Readers will encounter discussions on critical issues like public transparency or data privacy and ownership, along with the role of open-source in the new age of artificial intelligence. By examining these challenges, this text highlights remarkable opportunities for progress enabled by the open-source philosophy. This book aims, thus, to inspire and inform anyone interested in everything that surrounds this movement, from developers to designers and curious minds alike.